DIVING AS A HIGH-RISK SPORT: INJURY PREVENTION, SAFETY PROTOCOLS AND HUMAN FACTORS – A LITERATURE REVIEW - Łukasz Brzost; Marta Danuta Cendrowska; Justyna Berent; Karolina Stępień; Beata Choromańska; Barbara Ponitka; Paulina Rzepa; Julia Procyk; Aleksandra Klukowska; Julia Maszewska; Wiktoria Szumlińska; Szymon Milnerowicz (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Diving is a high-risk activity due to physiological and psychological stressors. This review addresses diving-related injuries and accidents, with particular emphasis on human factors and prevention strategies. Materials and Methods: We conducted a literature review (PubMed, 1995–2025) of studies on diving hazards (e.g., barotrauma, decompression sickness, drowning), psychological factors (anxiety, panic), human errors (miscommunication, overconfidence), and training and safety compliance measures. Results: Divers face barotrauma (ear, sinus, pulmonary), decompression illness, physical and thermal injuries, and drowning. Psychological stress (anxiety, panic) and human errors (communication failure, inattentiveness, overconfidence) contribute substantially to accidents. Many incidents involve cascading errors. Simulation-based training and adherence to evidence-based safety procedures have been shown to improve preparedness and reduce incidents. Conclusion: Effective dive safety requires addressing hazards and human error. Emphasizing adherence to dive protocols (ascent rates, decompression stops), clear communication, and error recognition is essential. Comprehensive training and the development of a safety culture are essential to mitigate risk and prevent injuries.